The billion dollar ransom - Dixon, Franklin W.; Copyright Paperback Collection (Library of Congress) (New York Simon & Schuster, 1982)
The Hardy boys help out when a magicians' tournament is threatened by mysterious happenings.
Keywords: Magic tricks -- Fiction; Children's stories..; Mystery fiction..